2012
DOI: 10.1143/apex.5.113002
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Order Dependence on Magnetocrystalline Anisotropy in Body-Centered Tetragonal FeCo Alloys

Abstract: We investigate the magnetocrystalline anisotropy (MCA) energy of tetragonal distorted FeCo alloys depending on the degree of order by first-principles electronic structure calculation combined with the coherent potential approximation. The obtained results indicate that the MCA energy of FeCo alloys strongly depends on the degree of order under optimal conditions, where the axial ratio of the bct structure is 1.25 and the composition is Fe 0.5 Co 0.5 . We find that the modification of the electronic structure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 22 publications
2
43
0
Order By: Relevance
“…In the present work, to confirm the above scenario, we calculate the MAE as a function of M for the tetragonally distorted (c/a = 1.2) FeCo disordered alloy [8,9], which was theoretically proposed by Burkert et al [8] to have large MAE. The FeCo disordered alloy is not a two-sublattice system, and it is completely different from the FePt system.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…In the present work, to confirm the above scenario, we calculate the MAE as a function of M for the tetragonally distorted (c/a = 1.2) FeCo disordered alloy [8,9], which was theoretically proposed by Burkert et al [8] to have large MAE. The FeCo disordered alloy is not a two-sublattice system, and it is completely different from the FePt system.…”
Section: Introductionsupporting
confidence: 65%
“…We selected MnAl because Al does not have strong SOI like Pt. Furthermore, as suggested by Kota et al, [9] the mechanisms of MAE occurrence for these systems differs. In this sense, the MnAl and FeCo alloys are adequate systems for investigating whether the model proposed by Mryasov et al is feasible.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…First-principles calculations have shown that Fe-Co alloy can have a high uniaxial magnetocrystalline anisotropy (K u ) of up to 10 7 J·m ¹3 when its lattice is distorted into a bct crystal structure. 21,22) The crystal structure of Fe-Co nanoparticles deposited on SiO 2 nanoparticles was therefore investigated by TEM. A high-resolution TEM image is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Based on the first-principle calculations, some groups predicted that tetragonal distorted FeCo alloy with a specific structure and alloy concentration resulted in a large uniaxial magnetic anisotropy. 6,7 On one hand, this distorted structure was expected to enhance the orbital magnetic moment by reducing the energy difference between d xy and d x 2…”
Section: Introductionmentioning
confidence: 99%